2014
DOI: 10.1039/c4cc00335g
|View full text |Cite
|
Sign up to set email alerts
|

A facile method for the synthesis of the Li0.3La0.57TiO3 solid state electrolyte

Abstract: We report a facile method for the synthesis of Li(0.3)La(0.57)TiO3 by forming a coagulated precursor solution which contains Li(+), La(3+), and TiO2 nanoparticles mixed highly homogeneously. The grain and overall conductivities of the synthesized Li(0.3)La(0.57)TiO3 are comparable to the values in literature for the material prepared by other methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Since Inaguma et al reported high lithium ion conductivity (1 9 10 -3 S cm -1 ) in lithium lanthanum titanate at room temperature [153], research is focused on studying lithium ion conduction of La 2/3-x Li x TiO 3 (LLTO). In the LLTO structure, the lithium ions diffuse in a three-dimensional network of vacancy defects located at A sites perovskite and this conduction is based on hopping process [154]. The lithium ionic conduction of LLTO is influenced by A-site vacancy defects, lithium and vacancy concentration, structural distortion, bottleneck size, and Ti-O covalent bond [153,[155][156][157].…”
Section: Outlook Lithium Ionic Conduction In Edltsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Inaguma et al reported high lithium ion conductivity (1 9 10 -3 S cm -1 ) in lithium lanthanum titanate at room temperature [153], research is focused on studying lithium ion conduction of La 2/3-x Li x TiO 3 (LLTO). In the LLTO structure, the lithium ions diffuse in a three-dimensional network of vacancy defects located at A sites perovskite and this conduction is based on hopping process [154]. The lithium ionic conduction of LLTO is influenced by A-site vacancy defects, lithium and vacancy concentration, structural distortion, bottleneck size, and Ti-O covalent bond [153,[155][156][157].…”
Section: Outlook Lithium Ionic Conduction In Edltsmentioning
confidence: 99%
“…Afterward, Yanagi et al fabricated the Fig. 26 Schematic comparison of black phosphorus transistor [154] with other different transistors [30,31,[160][161][162][163][164][165][166][167][168][169][170].…”
Section: Tuning Thermoelectric Properties In Transistorsmentioning
confidence: 99%
“…Thus, the larger grain size would reduce the overall resistance, resulting in higher ionic conductivity. Furthermore, theoretical analysis has suggested that the nearest-neighbor Li-ion hopping favors along the edge of the Li 6 O octahedron via Li vacancies, [ 17 ] i.e., the (011) planes in the cubic antiperovskite structure. This provides further support for the higher conductivity of the fi lm with larger grain size and a preferentially orientated growth along (011).…”
Section: Doi: 101002/advs201500359mentioning
confidence: 99%
“…In addition, the solid‐state electrolytes can be readily integrated with a metallic lithium anode, allowing solid‐state LIBs with potentially high energy densities. Thus far, solid‐state electrolytes have not been widely used in the commercial products because their ionic conductivities are not high enough to meet the requirements for high‐performance Li batteries . Hence, it is extremely important to develop advanced solid‐state electrolytes with high ionic conductivity and good compatibility with cathode and anode materials for all‐solid‐state LIBs.…”
mentioning
confidence: 99%
“…Nevertheless, solid electrolytes have not been extensively used in lithium batteries because their ionic conductivities are still too low to meet the requirements for efficient electric-energy storage. [8][9][10] In addition, high interfacial resistance between the solid electrolyte and electrode is yet another challenge for solid-state LIBs.…”
mentioning
confidence: 99%